Specifying Expected Learning Outcomes for Bachelor of Fine and Applied Art Program in 3D-Based Communication Design and Integrated Media through Delphi Method - Borriraklert, Atthaves; Ratanawijarn, Neerawan; Chaisiri, Danupop (Asian Creative Architecture, Art and Design, 2021)
Identifying the expected learning outcomes is a significant starting point for outcome-based education. Bachelor of Fine and applied art program in 3D-based communication design and integrated media, faculty of architecture, King Mongkut’s institute of technology Ladkrabang had considered the principle of outcome-based education in designing the curriculum, and planning the teaching and learning activities since 2016. The research objective is to specify the expected learning outcomes for the program revision in 2021 through Delphi method by gathering, analyzing, and synthesizing data from stakeholders into consensus that meet the requirements of the professional field in the job market. The data was gathered from 23 experts in 3D-based communication design and integrated media, and extracted into 31 factors of competency. Item-level content validity index (I-CVI) and modified Kappa statistic was performed to evaluate each factor validity and reliability. From the findings, 29 factors have excellent degree of validity and reliability, and the scale-level validity index of 0.927 indicates that the extracted factors are acceptable for specifying the program’s expected learning outcomes. The results from clustering extracted factors are 7 domains of expected learning outcomes those are (1) design principles and foundations, (2) creativity and design strategy, (3) design research, (4) content and storytelling through media, (5) design implementation, (6) design presentation and communication skills, and (7) design quality.